Validation of the New International League Against Epilepsy 2017 Classification for Determining Seizure Type in Indian Patients - Manorenj, Sandhya; Sagari, Navya (International Journal of Epilepsy, 2021)
Introduction Epilepsy is a common condition in neurology comprising several electroclinical syndromes and seizure disorders of varying known and unknown etiologies that require variable diagnostic workup, treatment, and have obviously different prognoses. Therefore, for appropriate patient management, the best possible classification system for epilepsy is required. The International League Against Epilepsy (ILAE) is continuously working on this with the latest classification provided in 2017. There is little knowledge about seizure type based on newer classification systems in Indian patients.Aims and Objective To test the applicability of the newer ILAE 2017 classification of epilepsy in determining seizure type in Indian patients, with respect to right patient management, the best classification system for epilepsy is necessary.Materials and Methods Prospective data of 310 consecutive patients with seizures presenting in neurology department was collected from December 2017 to June 2018 and analyzed according to the newer systems of classification of seizures proposed by ILAE in 2017.Results All 310 patients in age ranging from one year to 72 years with seizures could be classified according to the ILAE 2017 classification system. Focal onset seizure was noted in 66 patients (21.3%), while 244 patients (78.7%) had generalized onset based on clinical onset of seizure. Awareness was impaired in 262 (84.5%) patients. Motor onset seizure was observed in 278 patients (89.6%), while nonmotor seizure included absence, sensory, cognitive, and autonomic seizures.Conclusion The present study showed that all patients could be classified using ILAE 2017 classification system. Majority of seizure were generalized onset, predominantly motor type of seizure with impaired awareness using clinical description of classifying seizure, while focal onset seizure was the majority type of seizure when ancillary information was considered.
Keywords: seizures; epilepsy; classifications